In Memoriam Professors Marianna Sankiewicz-Budzyński and Gustaw K.E. Budzyński - Founders of the Polish Audio Engineering - CZYŻEWSKI, Andrzej; KOSTEK, Bożena (Archives of Acoustics, 2018)
Biography and scientific achievements of Professors Marianna Sankiewicz-Budzyński and Gustaw K.E. Budzyński - Founders of the Polish Audio Engineering.